Experimental and numerical investigation into the destemming of grapes - Lombard, Stephanus Gerhardus (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2011.